Protecting Civil Rights Amidst Rising Illiberalism in Indonesia’s Democracy: State’s Response to Sharia-Based Violence Against Shi’a Groups - M Khusna Amal (Ulumuna, 2020)
This article examines the local government and state representation in response to religious violence against Shi’a minority groups. Intensive scholarly debates on this issue have ignited, especially on what made the government showed an exclusive response to religious violence. Scholars have argued that state agencies commonly tend to take a safe position though no contradictory policies that please conservative groups. This research was conducted through six-month fieldwork in Bondowoso regency, East Java province, in 2017 and 2018. The data was collected through ethnography and in-depth interviews with relevant sources. In this study, I argue that not all government agencies respond exclusively to violence against minority communities. Through a case study on Sunni-Shi'a tension in Bondowoso, East Java, this study reveals that the local government showed inclusive attitudes to protect the rights of Shi'a adherents to practice their faiths. Such responses are aimed to maintain well-developed plurality, harmony, and civil rights for minority citizens of Bondowoso. This study confirms that inclusive local state officials become the critical factor to the sustainability of human rights, religious freedom for the minority and democratization.